(untitled) (Medico Legal Update, 2020)
Background: One of the most heinous ways of discrimination against women in a society is through female foeticide. The present study was conducted to assess knowledge and awareness regarding female foeticide among school children. Materials and Method: The present study was conducted on 580 school children of both genders. A self questionnaire was administered and all participants were asked to reply to assess knowledge and perceptions regarding female foeticide. Results: Out of 580 subjects, male were 320 and female were 260. 68% had correct knowledge regarding sex ratio, 65% had correct knowledge regarding district sex position, 67% had correct knowledge regarding state sex position and 74% had correct knowledge regarding foeticide definition. The difference was significant (P< 0.05). 76% replied correct that pre natal gender detection is crime, 72% replied that female foeticide should stop, 65% replied that female foeticide practice will harm society and 86% replied that pre natal gender detection is severely punishable act. The difference was significant (P< 0.05). Conclusion: Authors found students had sufficient knowledge and awareness about female foeticide.